2019
DOI: 10.3389/fgene.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Phenotypic Differences Between Chinese Yunling Black Goats and Nubian Goats Revealed by Allele-Specific Expression in Their F1 Hybrids

Abstract: Chinese Yunling black goats and African Nubian goats are divergent breeds showing significant differences in body size, milk production, and environmental adaptation. However, the genetic mechanisms underlying these phenotypic differences remain to be elucidated. In this report, we provide a detailed portrait of allele-specific expression (ASE) from 54 RNA-Seq analyses across six tissues from nine F1 hybrid offspring generated by crossing the two breeds combined with 13 genomes of the two breeds. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
3
11
0
1
Order By: Relevance
“…These genomic characteristics are important as a genomic basis for coping with future threats to the species arising from environmental change (Benjelloun et al, 2015), but are rapidly disappearing due to extensive crossbreeding and substitution with imported breeds. Therefore, to reveal their unique genomic characteristics, many genomic studies have been carried out in various indigenous livestock: cattle (Browett et al, 2018; Weldenegodguad et al, 2018); chicken (Johansson and Nelson, 2015; Walugembe et al, 2018); sheep (Yang et al, 2016; Edea et al, 2017); and goat (Benjelloun et al, 2015; Cao et al, 2019). In this context, our study focused on identifying KNG and revealed their distinct genomic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…These genomic characteristics are important as a genomic basis for coping with future threats to the species arising from environmental change (Benjelloun et al, 2015), but are rapidly disappearing due to extensive crossbreeding and substitution with imported breeds. Therefore, to reveal their unique genomic characteristics, many genomic studies have been carried out in various indigenous livestock: cattle (Browett et al, 2018; Weldenegodguad et al, 2018); chicken (Johansson and Nelson, 2015; Walugembe et al, 2018); sheep (Yang et al, 2016; Edea et al, 2017); and goat (Benjelloun et al, 2015; Cao et al, 2019). In this context, our study focused on identifying KNG and revealed their distinct genomic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The great variations in different phenotypic traits of two selected sheep breeds provide an opportunity for studying molecular mechanisms underlying gene expression related to phenotypic difference between thin-and fat-tailed sheep breeds. In this study, the candidate causative genes were detected by ASE analysis, which avoid the effect of trans-acting and has become research focus in recent years [24][25][26][27][28]. We divided all sheep individuals into 15 family trios.…”
Section: Discussionmentioning
confidence: 99%
“…Loci with both alleles < 100 reads and each allele in heterozygous sites with < 3 reads were filtered, which can remove loci exhibiting MAE and a relative lower expression [38][39][40]. Allelic read ratios were counted by a Python Script [27], significant allelic imbalances were identified using the cut-off criteria of allele ratio ≥ 0.65 or ≤ 0.35 [29], and statistical tests were conducted by…”
Section: Ase Analysis From Rna-seq Datamentioning
confidence: 99%
See 1 more Smart Citation
“…offs are introduced such as ratio of allelic read counts > 0.9 (Chamberlain et al, 2015) or > 0.7 532 (Cao et al, 2019). We decided to exclude MAE from this study using read count bi-allelic 533 expression filtration because it is difficult to distinguish between sequencing error and MAE.…”
mentioning
confidence: 99%